Pd-Catalyzed Formal [3+3] Annulation of Benzylic gem-Diacetates: Synthesis of Various (Hetero)Arene-Fused Benzo[ f]chromenes - Kumar, Prashant; Kumar, Pravesh; Venkataramani, Sugumar; Ramasastry, S. S. V. (ACS Publications, 2022)
Palladium-catalyzed allylic alkylation reactions of allylic gem-diacetates are rarely explored. This work unveils an unusual chemical reactivity pattern of allylic gem-diacetates and establishes them as new prototypes to synthesize complex benzo[f]chromene systems. Under the reaction conditions, the diacetates behave as 1,3-dicationic equivalents and undergo a [3 + 3] heteroannulation with 2-naphthols (and meta-substituted phenols) to produce novel polycyclic chromenes possessing spiro-, tri-, and tetrasubstituted carbon centers. The versatility of the method is demonstrated in the synthesis of several chromene-based bioactive natural products. Further, interesting photochromic properties of the new classes of benzo[f]chromenes are also discovered.
Only IISERM authors are available in the record.
Keywords: Photochromic Properties; Allylic gem-Diacetates; Natural Products